Sugar Sweetened Beverages Consumption among University Students of Bangladesh - Munmun Shabnam Bipasha; Tahsin Sharmila Raisa; Shatabdi Goon (Intelektual Pustaka Media Utama, 2017)
Drinking large amounts of sugary beverages can increase the risk of gaining weight and developing Type 2 diabetes, heart disease, and other metabolic diseases. This study examined the preference, prevalence and pattern of sugar sweetened beverages consumption among university students of Bangladesh. A cross-sectional study was carried out from February to April, 2017 among students attending in a private university of Bangladesh. One hundred fifty undergraduates responded (83.4% male, 15.9% female) in this study. Most students (95.4%) reported sugared beverage intake and 53.6% reported more than two days in a week intake. Male students were more likely than female students to report regular sugary beverages intake (85.4% vs. 14.5%). The main reasons for fast food consumption were: good taste and refreshing (80.1%), cost effective (6.6%), easy accessibility (2.6%), increased convenience (8.6%), peer influence (1.3%). Good taste and price were the most important factors in choosing beverages. Coca-Cola (49%), Fanta (25.8%), Sprite(9.9%) and Slice(14.6%) has been reported as mostly consumed beverages among students. Most students (54.5%) reported sugary beverages purchase from neighborhood convenient stores. 94.5% students said that if they would provide with healthful beverages within their food environment, they would prefer drinking healthful beverages (lemon water, non-sugary beverages) instead of sugar beverages. Self-reported sugar-sweetened beverage consumption among undergraduates is substantial and likely contributes considerable non-nutritive calories, which may contribute to weight gain. Specific health education programs, dietary guidelines and effective public awareness campaigns could be initiated to address the unhealthy drinking pattern of university students and improve their health.